Sustained censorship in IR (2026-05) (Iran) - Voidly (2026)
CRITICAL severity censorship detected in Iran. Confidence: 77%. Data sourced from OONI, CensoredPlanet.
Censorship Incident ID: IR-2026-0233
Keywords: censorship; IR; censorship; critical